Communication – a culture of open dialogue. Issue 1 (13th April 2015) - Jackson, Val; Perry, Alex
Abstract : Purpose: – Open dialogue (OD) is an innovative approach to mental health crises based on close collaboration between services and an individual's family and social network. The approach was originally designed by Jaakko Seikkula and his colleagues in Tornio, Finland and is now being developed in many countries around the world, in particular Denmark, Germany, Norway and the USA. OD describes both a way of being with families and also a way of organising services aimed at maximising communication and connection. The purpose of this paper is to describe the principles of OD, it's development in Finland and here in the UK. Design/methodology/approach: – This paper is a description of the principles and outcomes of OD as practised in Western Finland. It also describes the recent developments in the UK using the approach. Findings: – This paper is descriptive of the model and is not of a research project. Originality/value: – Whilst care must be taken in assuming that these remarkable results are transferable to the UK, other countries and several Mental Health trusts in England are actively engaged with developing an OD approach.